Cover Image, Volume 5, Issue 1. (January 2016) - Unknown
Abstract : The cover image, by Viola Walther and Malcolm R. Alison, is based on the Advanced Review "Cell lineage tracing in human epithelial tissues using mitochondrial DNA mutations as clonal markers", DOI10.1002/wdev.203 .